Pengaruh Faktor Fundamental dan Risiko Sistematis terhadap Harga Saham Sektor Trade Service and Investment - Steven Steven; Muhammad Ghazi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research have purpose to test the factors that influence company’s share price. Independent variables in this research consist of Return On Equity, Price Earning Ratio, Debt to Equity Ratio, Earning Per Share, Net Profit Margin and Systematic Risk. The data for this research are Trade Service and Investment listed on the Indonesia Stock Exchange (IDX) for the period 2013 to 2019. This research uses 98 samples and the sample selection method used is the purposive sampling method. This research test uses multiple regression analysis. Based on the results of the reseach, it can be concluded that Price Earning Ratio and earning Per Sharehaspositive effect on Stock Price, where an increase in Price Earning Ratio and Earning Per Share will increase the Stock Price. However, Return On Equity, Debt to Equity Ratio, Net Profit Margin, and Market Price have no effect on Stock Price.